Life. - Berndt, Jaqueline; Hata, Yoshiko; Mogi, Ken; Takahashi, Mizuki (Mito-shi : Contemporary Art Center Art Tower Mito Mito-shi, 2006)
Akira the Hustler ; Hino, Korehiko ; Imamura, Hanako ; Kawashima, Hideaki ; Nishio, Yasuyuki ; Okazaki, Kyoko ; Saito, Yuichi ; Sasaki (Heartbeat Drawing) ; Sasaki, Takuya ; Syuji, Takashi ; Tanada, Koji ; Yamagiwa, Masami ; Yoshinaga, Masayuki
Japanse tekst + apart Engelse vertaling
biog. p. 27-29 (English Supplement)
Japans
Engels
Exhibition. Life. Contemporary Art Center Art Tower Mito Mito-shi. 22.07. 2006 - 09.10.2006
boek
Keywords: Japan